Implementation of The Accounting Cycle in the Bungsu Bengkulu Award Business Based on the EMKM SAK - Violanda Rizqi; Anisa Vionita; Hendri; Tiara Atika; Jamila (Jurnal Aghniya, 2025)
Background: Micro businesses like Angkringan Bungsu Bengkulu usually keep simple, informal records. This study evaluates the implementation of the SAK EMKM accounting cycle to improve financial transparency and accountability. Method: Qualitative descriptive; primary data from owner interviews, secondary data from September 2025 invoices and daily sales records. Analysis followed the accounting cycle: journal, ledger, trial balance, adjustments, and financial statements. Results: September transactions: raw-material purchases Rp700k, cash sales Rp2.3m, utilities Rp150k, equipment Rp500k. After adjusting for depreciation (Rp100k) and accrued rent (Rp200k), net profit was Rp1.05m, total assets Rp5m, liabilities Rp200k, equity Rp4.8m. Conclusion: Applying the SAK EMKM accounting cycle provided timely financial statements, enabled the owner to know exact profit, assets and liabilities, and upgraded business management toward professional and sustainable growth.